The Ranking of the Western Balkan Countries According to the Degree of Globalization - Zendelovski, Goran (Prizren Social Science Journal, 2021)
Globalization does not have the same impact on countries, it acts differently in countries with different levels of political, economic, social and technological development. Its unequal distribution by region, country or community confirms that it is a complex and deeply asymmetric process. It is confirmed by numerous theories and debates that only explained and defined the phenomenon, but paid little attention to the complexity of globalization and measuring its extent. Empirical indicators can be used to measure the differences between the national and the international in different domains. In this way, it is possible to see to what extent the countries are globalized, i.e., to see the strong influence of globalization processes on the overall state of society. That is why a large number of countries try to use the processes of globalization to promote national interests and improve their position in international relations. Therefore, the analysis of the indexes of globalization will help us to understand with which components of national power the countries dominate on the regional and global scene. The focus of the research is on the analysis of several globalization indexes that include the countries of the Western Balkan. Namely, the degree of globalization of countries is empirically analyzed through the prism of several different indicators that are constructed to measure the overall index of globalization, as well as to measure the political, economic and social dimension of globalization. The inclusion of a larger number of variables enables a more objective and accurate ranking of countries. As the results of the globalization rating of the Western Balkan countries show, it is concluded that the processes of globalization greatly contribute to strengthening and improving cooperation between countries, intensify interdependence, affect Euro-Atlantic integration processes, stimulate economic growth and improve the situation in societies. However, according to the elaborated data, these countries are still in the phase of adjustment or “maturation”, therefore, they are in the category of partially globalized countries.
Keywords: Variables, Rating, Indexes, Globalization, Western Balkans.